Labour mobility in the EU: Dynamics, patterns and policies - Mikkel Barslund; Matthias Busse; Carlos Vargas-Silva; Pawel Kaczmarczyk; Timo Baas; Mario Izquierdo Peinado; Juan F. Jimeno; Aitor Lacuesta; Béla Galgóczi; Janine Leschke (Intereconomics, 2014)
The continued economic crisis has become a major test for the labour markets of individual member states. Labour mobility within the European Union has the potential to help to reduce labour market pressures and ease economic imbalances. However, a long-term loss of working age population can be detrimental to sending countries. This Forum explores mobility patterns within the European Union and analyses the labour market and welfare effects of labour mobility via case studies of the UK, Poland, Germany and Spain. It also examines a number of its aspects that have important political and institutional relevance for the European Union and its future.
Keywords: 330